Analysis Of Drying Eqipments For Drying Products - Safarov J.E., Sultanova Sh.A., Samandarov D.I., Jumayev B.M., Zulpanov Sh.U. (International Journal of Advanced Science and Technology, 2020)
The article is devoted to the characteristics of silkworm cocoons, it presents the stages of cocoon formation and the properties of silk fibers. In particular, the difference in thermal conductivity in different types of fibers and in different directions of the same fiber is explained. The thermal conductivity in the axial direction is higher than in the radial one; heat can be easily conducted in the direction of the macromolecular chain, but not in the direction perpendicular to it. Heat transfers through molecular collisions in the radial direction, which reduces the rate of thermal conductivity. The properties of silkworm cocoons, such as mechanical strength and gas properties, were investigated; but there are no scientifically based explanations of the reasons for ensuring that the cocoon has a high level of thermal insulation. Therefore, first of all, the details of the construction of the wall of the cocoon were investigated. Based on the presented material, it can be concluded that the vibrating IR-drying unit has a number of significant advantages and can be successfully used in organizing industrial drying of not only cocoons, but also various kinds of products in a “gentle” mode.